2021
DOI: 10.1002/jsfa.11255
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils and their nanoformulations as green preservatives to boost food safety against mycotoxin contamination of food commodities: a review

Abstract: Postharvest food spoilage due to fungal and mycotoxin contamination is a major challenge in tropical countries, leading to severe adverse effects on human health. Because of the negative effects of synthetic preservatives on both human health and the environment, it has been recommended that chemicals that have a botanical origin, with an eco‐friendly nature and a favorable safety profile, should be used as green preservatives. Recently, the food industry and consumers have been shifting drastically towards gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 117 publications
(97 reference statements)
0
21
0
1
Order By: Relevance
“…EOs have antifungal, antiviral, antibacterial, antimutagenic, or antioxidant properties, and therefore, have a wide application in food industry and agriculture [ 18 ]. As essential oils are natural substances and can affect the growth, sporulation, and even the production of mycotoxins by filamentous fungi [ 19 ], they are promising and suitable alternatives to solve the problem of coffee contamination by fungi and their mycotoxins, as well as in other food commodities.…”
Section: Introductionmentioning
confidence: 99%
“…EOs have antifungal, antiviral, antibacterial, antimutagenic, or antioxidant properties, and therefore, have a wide application in food industry and agriculture [ 18 ]. As essential oils are natural substances and can affect the growth, sporulation, and even the production of mycotoxins by filamentous fungi [ 19 ], they are promising and suitable alternatives to solve the problem of coffee contamination by fungi and their mycotoxins, as well as in other food commodities.…”
Section: Introductionmentioning
confidence: 99%
“…However, application of Z. armatum EO in the management of A. alternata-induced tomato fruit rot is least explored. Green consumerism awareness and desire among common people having fewer synthetic food additives and products and minimum impact on the environment further advocate the use of EOs for the management of fungal pathogens in edible crops (Dangl and Jones, 2001;Anupama et al, 2019;Singh et al, 2021;Tao et al, 2021). Objectives of the present investigation were set forth to evaluate the efficacy of Z. armatum DC fruit EO in controlling the A. alternata-mediated rot in tomato fruits, vis-a-vis its role in modulating antioxidant potential of tomato fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural and eco-friendly methodologies for food preservation have been proposed in the last few years, but only limited data are available about the usefulness of most of them under industrial scale conditions, which needs proper attention to satisfy the requirements of the industry as well as the demand of the consumers [226][227][228][229][230]. Consequently, studies about the ability of the reported biopreservative agents to control the development of undesirable microorganisms when applied at the industrial scale are greatly required.…”
Section: Discussionmentioning
confidence: 99%